Eksplorasi matematika pada al-quran surat al-muthaffifin - Wahyuni, Tri; Nabila, Almira Tasya; Masamah, Ulfa (Maliki Interdisciplinary Journal, 2026)
Mathematics taught in schools is often not associated with problems that are relevant to students' daily lives, even though mathematics is actually a science that can be applied in various aspects of life. In addition, mathematical concepts are also found in the Qur'an, which can be utilized in the learning process. This study aims to explore and identify mathematical materials contained in the Al-Muthaffifin letter. This study uses a qualitative approach with a library or literature study method. The main data sources for the study are the Qur'an and related articles. The main instrument used is the researcher himself, with documentation guidance as a supporting instrument. Data were collected through documentation, especially collecting articles that connect mathematics with the verses of the Qur'an. The data analysis technique uses the miles & huberman model. The results of this study indicate that several mathematical concepts contained in the Al-Muthaffifin letter include measurement, mathematical logic, statistics, and asymmetric relations. Therefore, mathematics learning can be integrated with the values or verses of the Qur'an. For example, the concept of measurement can be linked to scales in buying and selling. With the discovery of mathematical material in the letter Al-Muthaffifin, it is hoped that this can support the integration of the verses of the Qur'an in mathematics learning, both as apperception and other parts that are useful for the learning process.